Pengaruh Tekanan Karyawan dan Struktur Kepemilikan terhadap Kualitas Sustainability Reporting - Wilia Kastuti; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze the effect of employee pressure and ownership structure on the quality of sustainability reporting. The quality of the sustainability report is measured using a disclosure index. Employee pressure is measured by the number of employees. While the ownership structure in this study is represented by foreign ownership as measured by the number of shares owned by foreigners compared to total outstanding shares, highly controlled equity is measured by equity attributable to owners of the parent entity compared to total equity, and foreign-oriented companies as measured by foreign subsidiaries compared to the number of subsidiaries. The population of this research is all companies listed on the Indonesia Stock Exchange in 2016-2020 which publish sustainability reporting using a sampling method, namely purposive sampling so the final sample of this study is 35 companies. The analysis technique used is multiple linear regression analysis. Overall, the results of this study indicate that employee pressure does not affect the quality of the sustainability report. The ownership structure, namely foreign ownership, highly controlled equity, and foreign-oriented companies also do not affect the quality of the sustainability report.